Pengaruh Kualitas Pelayanan dan Promosi Terhadap Keputusan Pembelian Mobil Suzuki Carry Pick Up Pada PT. Sejahtera Indobali Trada Di Kabupaten Tabanan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The rapid development of the automotive industry has intensified competition, particularly in the car sector. Authorized Brand Holders (ATPM) for cars continue to innovate their products. The aim of this research is to analyze the factors influencing the purchasing decision of Suzuki Carry Pick Up at PT. Sejahtera Indobali Trada in Tabanan Regency. The study involved 70 individuals who had purchased Suzuki Carry Pick Up at PT. Sejahtera Indobali Trada in Tabanan Regency, constituting an infinite population where the number is unlimited. Data collection was done through questionnaires. The analytical technique employed was multiple linear regression analysis to examine the influence of service quality and work discipline on the purchasing decision of Suzuki Carry Pick Up at PT. Sejahtera Indobali Trada in Tabanan Regency.The results of hypothesis testing indicate that service quality has a positive and significant impact on the purchasing decision of Suzuki Carry Pick Up at PT. Sejahtera Indobali Trada in Tabanan Regency. The second hypothesis suggests that promotion has a positive and significant influence on the purchasing decision of Suzuki Carry Pick Up at PT. Sejahtera Indobali Trada in Tabanan Regency. The third hypothesis indicates that both service quality and promotion have a positive and significant impact on the purchasing decision of Suzuki Carry Pick Up at PT. Sejahtera Indobali Trada in Tabanan Regency.Suggestions for PT. Sejahtera Indobali Trada include focusing on employee training and development, enhancing professional communication, and being responsive to customer inquiries. Improving the physical condition of the showroom and vehicle presentations can enhance customer perception of product quality. In promotions, there is a need for increased frequency and diversification of promotional media, emphasizing unique features of Suzuki Carry Pick Up, and regular evaluation of promotional strategies. For future research, it is recommended to add independent variables such as consumer perceptions and attitudes, as well as trends in purchasing decisions. The research scope may include other types of companies for diversity, and it is essential to increase the sample size for broader insights into purchasing decisions.